Implementasi System Development Life Cycles (SDLC) Aplikasi Keuangan dan Perluasan Pemasaran Berbasis Digital Pada Kelompok Pelaku Usaha Binaan Koperasi IBS Jakarta Selatan - Santi Rimadias; Bani Saad; Deni Wardani; Ossi Ferli; Adelya Vasya Maharani; Abraham Reinhard Lapondu; Annisa Nur Azima Zulfa (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The group of business actors fostered by the IBS Cooperative is located at the Indonesia Banking School Campus, Jalan Kemang Raya No.35, South Jakarta. Members of this group include Mirasa, Warung tom-tom, Burger Crepes, Warung Sunda, Ayam Penyet Mas Nok, and Warung Solo Bu Wiwid. The main problem of this group of business actors is still using the manual financial reporting method. In addition, the main problem they face is a limited understanding of marketing promotion. To overcome this problem, training and financial assistance are carried out based on System Development Life Cycles (SDLC) and the expansion of digital marketing. SDLC will help improve efficiency and accuracy in the preparation of financial statements, while digital marketing training will enable businesses to optimize online marketing strategies. Through the implementation of this training and mentoring, the IBS Cooperative fostered business actors are able to improve business performance through the use of SDLC technology and more effective digital marketing. This activity also involves partner participation, evaluation, and program sustainability to ensure successful implementation.